2021
DOI: 10.2147/jmdh.s311900
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Illness and Treatment Decision Modelling During Ill-Health in Arabic Families

Abstract: Background: The use of self-prescribed antibiotics and other unproven herbal remedies is common in the Arab world. Understanding how family members decide to manage illness is an important priority for health care providers. Purpose: This paper presents a new model that can be viewed as an extension to the Health Belief Model and help clarifies the cognitive processes families use to manage illness in an Arab family in Jordan. It aims to generate an understanding of family beliefs about the causes of illness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…One explanation for the results, although expected, is related to components of JLS that enhance integration, interaction, and reflective skills of learning among students. At the same time, traditional lecturing will indirectly force students toward one-way communication, which may lower their problem-solving skills and creativity [18]. The results regarding the effectiveness of JLS are inconsistent in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the results, although expected, is related to components of JLS that enhance integration, interaction, and reflective skills of learning among students. At the same time, traditional lecturing will indirectly force students toward one-way communication, which may lower their problem-solving skills and creativity [18]. The results regarding the effectiveness of JLS are inconsistent in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no patients who died because of COVID-19 were included in this study. A study conducted among Thai older adults during the COVID-19 crisis found that, besides physiological problems, religion, self-management, and emotional management were positively associated with spirituality and resilience (Arabiat et al, 2021; Soonthornchaiya, 2020). In this study, we identified positive thinking, optimism, and religiosity as major contributors to recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the local medical system in southern China classifies constitutions and symptoms into ‘cool’ or ‘hot’ nature and applies prescriptions with herbs or foods antagonistic to these nature [ 20 , 45 ]. These informal self-treating, which are often accessible, inexpensive and effective, have embedded in the memories of older people through word-of-mouth cases and have become widely accepted as alternative medical treatments [ 46 ]. Hence, the older adults in rural were prone to empirical self-treatment over seeking help from the modern healthcare system [ 7 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%